The Radiographic Changes in CBCT Image as predictors of osteoporosis - أحمد كرم; عبد الكريم خليل (Latakia University Journal -Medical Sciences Series, 2023)
Bone is living tissue, it consistently underergoes modeling and remodeling to withstand functional demands. Differences in hormones influence bone quality and quantity particularly through post menopausal leading to susceptibility to osteoporosis. This study was conducted to investigate the width and density of the mandibular cortical bone as diagnostic indicators for diagnosing osteoporosis in the elderly using Cone Beam Computed Tomography (CBCT). The research sample included two groups: the study group consisted of (10) patients diagnosed with osteoporosis according to the T-Score scale, where their T-Score value smaller or equal -2.5 at ages 45-61 years, and the control group consisted of (12) individuals Healthy people aged 48-60 years with a T-Score greater or equal to -1.Each of following variables was evaluated: MI and CI on CBCT image.The results showed statistically significant differences in the values of MI and CI between osteoporotic patients group and control group, meaning that there is a correlation between the values of MI and CI and mineral density of the lumbar spine.